Synthesis of compounds containing Cyano Anchor Groups, production of dye-sensitive solar cells and invesigation of the antibacterial properties of these compounds - Aytan Kilicarslan, Fatma; Altikatoglu Yapaoz, Melda; Erden, Ibrahim (YILDIZ TECHNICAL UNIV, 2026)
Global warming has become one of the most important factors threatening the world. The first place among the causes of global warming is taken by fossil fuels, which are mainly used for energy needs. The intensive consumption of fossil fuels causes the decrease of the world's fossil fuel reserves, environmental pollution and the greenhouse effect. Various renewable energy sources are shown as alternatives as a solution to these problems. Among all renewable energy forms, solar energy is the most popular. In this article, a dye-sensitive solar cell device of two compounds having a cyano anchor group containing fluorene and triphenyl amine as donor groups was prepared, and their antibacterial properties were investigated. The photovoltaic and electrochemical properties of these materials were evaluated, and it was investigated whether they could be used as photosensitizers in dye-sensitive solar cells. Photovoltaic cell efficiencies of the devices were in the range of 0.13-0.04% under 100 mW/cm2 simulated AM 1.5 solar irradiance, and the highest open circuit voltage reached 0.45 V. When the photovoltaic cell efficiency values of the produced dye-sensitive solar cell devices were examined, it was seen that the L1 compound was higher than L2 due to the effect of the donor group. The antimicrobial properties of L1 and L2 compounds were examined, and the effect of donor groups was investigated. The conventional disk diffusion method was used to evaluate the antibacterial activity of the synthesized compounds against Escherichia coli and Staphylococcus aureus. As a result, it was seen that the produced compounds showed antibacterial activity, and the compound with high photovoltaic cell efficiency value had a high antibacterial properties.
Keywords: Antibacterial Activity; Dye Sensitized Solar Cells (DSSCs); Fluorene; Triphenylamine; SCHIFF-BASES; LOW-COST; DERIVATIVES; DIAMINOMALEONITRILE; ABSORPTION; Engineering